2021
DOI: 10.1038/s41419-021-04390-4
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell transcriptome profiling reveals intratumoural heterogeneity and malignant progression in retinoblastoma

Abstract: Retinoblastoma is a childhood retinal tumour that is the most common primary malignant intraocular tumour. However, it has been challenging to identify the cell types associated with genetic complexity. Here, we performed single-cell RNA sequencing on 14,739 cells from two retinoblastoma samples to delineate the heterogeneity and the underlying mechanism of retinoblastoma progression. Using a multiresolution network-based analysis, we identified two major cell types in human retinoblastoma. Cell trajectory ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 50 publications
(58 reference statements)
1
17
0
Order By: Relevance
“…Consistent with previous scRNA-seq studies in RB 5,11,12 , our results highlighted high intratumoral heterogeneity in RB. We identified 10 subpopulations representing different stages of RB with varying malignancy.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Consistent with previous scRNA-seq studies in RB 5,11,12 , our results highlighted high intratumoral heterogeneity in RB. We identified 10 subpopulations representing different stages of RB with varying malignancy.…”
Section: Discussionsupporting
confidence: 92%
“…Early mouse studies suggest that RB can arise from amacrine cells 84 , horizontal cells 85 or Müller glia cells 86 . In contrast, recent studies point to cone precursors as the origin of RB in humans 5,11,12,20 . Consistent with this, we showed a dominant presence of cone precursors in RB tumor, as well as presence of highly proliferated cone precursors, CAFs and glial cells to form a complex TME.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Therefore, it is important to understand how the intratumoral heterogeneity and microenvironment are related to the occurrence and malignant degrees of RB, which will facilitate development of new treatment strategy of RB. Recently, two RB single-cell studies [ 22 , 23 ] discussed the heterogeneity of RB tumors. Because these two studies included only two samples, with a relatively small number of cells (8086/14,739), they did not identify many rare cell types, such as CAF, TAM, and astrocyte-like, which had been confirmed to exist in RB [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Collin et al [ 22 ] revealed G2/M cone precursors as the cell of origin in RB. Yang et al [ 23 ] revealed that the RB cells originated from the cell cycle-assoicated cone precursors. However, due to the limited number of cells (8086/14,739) and samples (two samples) in these two studies, how the malignant progression in RB is determined by the heterogeneity of tumor cells and TME remains uncharacterized.…”
Section: Introductionmentioning
confidence: 99%